Second Language Pedagogy and Translation: The Role Of Learners' Own-Language and Explicit Instruction Revisited - Kupske, Felipe Flores (BELT - Brazilian English Language Teaching Journal, 2015)
Translation has been a core of controversies on whether it can be a valid and effective instrument in second language (L2) teaching. This work advocates the movement that tries to restore translation as a practical and efficacious pedagogical tool. In order to do so, the reasons why translation was rejected are presented with a focus on the ban of the L1 use in L2 educational settings. However, this study also presents some contemporary debates about the use of L1 in language pedagogy and its productive role in language teaching. Therefore, drawing on ideas from discussions on the role of L1 and the explicit instruction, are able to review the translation status, and that its use is pertinent in L2 teaching and learning in a justified, organic and contextualized manner.